Competition for Land: The Water-Energy-Food Nexus and Coal Mining in Mpumalanga Province, South Africa - Simpson, Gareth B.; Badenhorst, Jessica; Jewitt, Graham P. W.; Berchner, Marit; Davies, Ellen (Frontiers in Environmental Science, 2019)
The Mpumalanga Province is a key source of South Africa’s coal supply with over 60% of the province’s surface area either being subject to mining rights or prospecting applications. Mpumalanga also possesses almost half of the country’s high potential arable land. While South Africa is currently largely self-sufficient in terms of cereal grains, what this assessment of Mpumalanga highlights is that food security is increasingly being threatened by coal mining interests that serve the nation’s energy needs. Water availability and quality for mining, agriculture and energy production in this province are also becoming increasingly strained. The water quality deterioration generally results from either acid mine drainage or contaminated runoff from mines and agricultural lands. This assessment of Mpumalanga highlights the interconnectedness of energy, food and water security, with their resultant trade-offs. The water-energy-food (WEF) nexus provides a focussed lens through which to evaluate resource security in a holistic manner. Only once regulators, NGOs, industry and the public view the resource security challenges in Mpumalanga in an integrated manner can planning and policies that lead to sustainable development be advanced, and objectives such as the Sustainable Development Goals be achieved. There is, therefore, a need for WEF nexus science and data to influence integrated public policy within this province.